Meningkatkan Aktivitas Dan Karakter Disiplin Menggunakan Model Paten Pada Siswa Kelas IV SDN Teluk Dalam 11 - Herdyan Azoka Chandra; Akhmad Riandy Agusta (CV. ITTC INDONESIA, 2024)
The main problem of learning given by teachers so far tends to only use the lecture method and learning is still one-way, as well as the lack of active student roles, student activities, and the use of media during learning. This has an effect on the low student activity, student discipline skills and learning outcomes of fourth grade students at SDN Teluk Dalam 11 Banjarmasin. Through the PATEN model (Problem Based Learning, Numbered Heads Together and Contextual Teaching Learning) which is an alternative solution to problem solving. The purpose of this research is to improve students' discipline skills and student learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research (CAR). The subjects of this study were fourth grade students at SDN Teluk Dalam 11 Banjarmasin, while the number of students was 7 people. While collecting data on teacher and student activity and student discipline skills was obtained through observation sheets, and student learning outcomes were obtained through individual tests. Data analysis in this study used descriptive analysis techniques translated into tables, graphs and interpretations with percentages. The results showed that teacher activity at meeting I got a score of 36, meeting II got a score of 38, and at meeting III got a score of 40. Student activity at meeting I got a percentage of 43%, at meeting II got a percentage of 57%, and at meeting III got a percentage 86%. Meanwhile, students' discipline skills at meeting I obtained a percentage of 57%, meeting II obtained a percentage of 71%, and at meeting III obtained a percentage of 86% classically. Based on the results of this study it can be concluded that the PATEN model (Problem Based Learning, Numbered Heads Together and Contextual Teaching Learning) can increase student activity, discipline skills and student learning outcomes.